EARLY DIAGNOSIS OF CARDIOVASCULAR DISEASE IN ATHLETES - Nurboev F. E; Ismoilova M.Yu. (International Engineering Journal For Research & Development, 2020)
In athletes, pathology of the cardiovascular system occupies a leading position in terms of their incidence. Functional changes in the cardiovascular system are an early sign of a change in the state of adaptation in the body of a trained athlete, and decreased ability to work, manifested by clinical signs of certain diseases in this system. In this article, a survey was conducted in athletes for early diagnosis of cardiovascular disease